(untitled) (Journal of Pharmaceutical Negative Results, 2022)
As a rule, flour confectionery products, which include cakes, are in great demand among almost all age groups of the population. The purpose of research was to develop a recipe and technology for the preparation of cakes using herbal additives from balm. Research methods that common for laboratories of confectionery factories were used. An aqueous extract and powder from the aerial part of balm were prepared. The effect of these additives on the contaminating microflora of flour and other recipe components of cakes was studied. The results of organoleptic and physical-chemical indicators of the quality of finished products and changes in the process of its storage are presented. It has been established that the quality indicators of prototype cakes met the requirements of GOST 15052-2014 “Cakes. General technical conditions”. The authors consider it possible to use herbal additives from balm in the production of cakes while maintaining the required organoleptic and physical-chemical indicators.